SISTEM PAKAR DIAGNOSA KERUSAKAN MOTOR YAMAHA NMAX MENGGUNAKAN METODE FORWARD CHAINING - Wiwid Wahyudi; Khoirur Rozikin; Afriliawan Indra Permana (STEKOM PRESS, 2020)
The recruitment of new mechanics at Mataram Sakti is no longer through the training process at the head office, but new mechanics are placed at the dealership accompanied by the chief mechanic as a supervisor, with the aim of providing training to new mechanics in order to be able to service or periodically repair Yamaha products especially the latest motorbikes namely Yamaha NMAX, because of the flurry sometimes the mechanical head is not in place so that when the mechanic is experiencing problems it cannot directly ask the mechanical head causing the handling of repairs to be less effective and efficient. One way to overcome this is to create a web-based expert system application with a forward chaining method so that the chief mechanic can transfer the knowledge he has into the computer. Forward chaining method is a search technique that starts with known facts and then matches these facts with the IF part of the IF-Then rules, so that conclusions can be drawn. This expert system was built using supporting software including, Macromedia Dreamweaver MX, PHP script language, MySQL database and WAMP server. The expert system for diagnosing damage to Yamaha NMAX motorcycles using the forward chaining method can be used as a new mechanical learning media in diagnosing damage to NMAX motorcycles and as a means of chief mechanics transferring their knowledge.